DETERMINATION ROCK DENSITIES OF ULUBELU GEOTHERMAL LAMPUNG BY USING GRAVITY METHOD COMBINED WITH BOREHOLE METHOD - Suharno, Suharno; Danusaputro, Hernowo (BERKALA FISIKA, 2006)
The Ulubelu geothermal system is located within Tanggamus volcanism. Rock densities were measured from wells Rendingan (Rd), Kukusan I (Kk1), Kukusan II (Kk2), Ulubelu II (UBL2) and Ulubelu III (UBL3). A terrain density estimate was made across line GG’ using the Nettleton method. The measured densities results, show values ranging between 2.60 x 103 kg m-3 and 2.70 x 103 kg m-3. The density estimated profile is presented in Figure 2 shows the density of about 2.70 x 103 kg m-3. Combined with the results from the laboratory measurements of borehole samples and density estimated, those suggest as the mean density of upper continental crust commonly used for the reduction of Bouguer anomalies (2.67 x 103 kg m-3).